Methods for Predicting Bubble Size Distribution in Turbulent Flow - Pengcheng Li; David Z. Zhu; Hang Wang; Rongcai Tang (Water Resources Research)
Abstract Gas bubbles are commonly observed in both natural and human‐made water systems, and their generation and distribution play pivotal roles in water quality and aquatic habitats. This study explores methods for predicting bubble size distribution within various types of turbulent flows. Models for bubble size distribution, both with and without bubble breakup, are developed and validated using experimental data from flows featuring return rollers at hydraulic jumps, skimming flows in stepped spillways, and bubbly flows in plunging jets. The experimental measurements reveal that turbulence kinetic energy dissipation rate, air void ratio, and Weber number influence bubble size distribution. These parameters are utilized to formulate the bubble size distribution model. When bubbles remain stable without breakup (i.e., when the Weber number is less than the critical Weber number), bubble size distribution at points and transects within fully developed turbulent flows can be accurately predicted. When the Weber number exceeds the critical value, the process of bubble breakup is considered to estimate the bubble size distribution. Additionally, numerical methods using the population balance model demonstrate that the initial bubble size fraction has minimal influence on the ultimate distribution in fully developed turbulent flows, while the air void ratio significantly impacts bubble size distribution. This study addresses the applicability and limitations of the bubble size distribution models and comprehensively discusses the advantages and disadvantages of each method, providing recommendations for their selection in both research and engineering applications.